Strategy for developing the potential of palm sugar in Malati village as a tourism destination in Naringgul district, Cianjur regency - Melvin Badriansyah; Reiza D. Dienaputra; Bambang Hermanto; Kurniawan Saefullah; Yustikasari (Jurnal Pariwisata Pesona, 2026)
Malati Village, located in Naringgul District, Cianjur Regency, possesses significant local economic potential through its sugar palm production. This commodity serves as the main livelihood for most residents; however, its management remains suboptimal due to limited firewood availability, the use of traditional tools, and a lack of product promotion. The study focuses on assessing current realities and outlining strategic steps for advancing sugar palm as a key local product, employing the Participatory Action Research (PAR) approach in the process.The process involved the Village Head and sugar palm artisans as key participants in reflection and action-planning activities. Data were obtained through on-site observations, detailed interviews, and documentation carried out collaboratively with participants. The results indicate that sugar palm processing in Malati Village continues to rely on traditional techniques, beginning with sap collection and ending with manual molding. Despite its simplicity, the process holds considerable economic and cultural value for the community. Through the PAR stages, reflective discussions were conducted to determine development initiatives, including capacity-building for artisans, improvements in production methods, and product promotion through visual documentation facilitated by the researcher.Collaboration between the village government and sugar palm artisans through a participatory approach produced development strategies that are contextual, sustainable, and rooted in local wisdom.